The Weakening of Taxpayer Rights in the Exchange of Information between Tax Authorities - Selicato, Gianluca (Review of European and Comparative Law, 2024)
Developments in international legislation and the growing digitalization of tax law support the development of global networks between tax authorities. We are witnessing an integration of databases that will lead to increasingly intense coordination of the fight against tax evasion at a supranational level. As in social networks and digital commerce, databases are increasingly enriched, contain increasingly precise information on the individual taxpayer and use common languages that allow for automated exchanges of information. While waiting for the creation of a global database – not conditioned by the constraints of reciprocity and abstractly usable by all authorized entities who need it – the first risks of limitation of the taxpayer’s rights are emerging. In fact, these phenomena have dark sides that are starting to emerge in use, at a national level and with respect to individual taxpayers, of interpolated databases. Moreover, a growing amount of information flows from heterogeneous and increasingly widespread sources, sometimes not protected by the requirements of professionalism, legality and public trust since data collection and entry can be delegated to economic entities, intermediaries and consultants. The absence of an authority responsible for the unitary management of global databases and for the resolution of their conflicts, the slow and timid affirmation (only in some national systems) of the taxpayer’s right of access to information concerning them, the difficult configuration of the faculty to request the correction of erroneous data and of the specular public power to remove the reported inaccuracies, weaken the system of protections gradually erected to protect the taxpayer’s position. In this way, the coordination of national systems that contemporary tax law creates is strongly unbalanced on the side of the protection of tax interests. International and European tax law should instead provide greater guarantees in favor of the taxpayers, defending their right to fair taxation.